El liderazgo y su incidencia en los procesos de formación de los estudiantes de la Institución Educativa Bachillerato Mixto de las Nieves. (2010)
This work is to design educational strategies for developing leadership, promoting and implementing training throughout the educational process for students and teachers. This qualitative research is aimed at solving a educational problem, describes the characteristics of a phenomenon sociable as education. Being also a type of research where we applied ethnographic field notes, interviews and surveys. The results to the question "What do you mean by leadership? 70% of parents answered ¨ "attribute to represent a group of people to seek a common good by addressing the students with the same question responded "to help a group d students for mutual benefit of the institution, "the same question was asked of teachers and 90% answered "strength of a individual (leader) to guide a set of actions to benefit the educational community. " In these responses can be observed for understanding leadership concept which means "an individual has capacity to influence a group of people doing this work enthusiasm in pursuing common goals. Leaving assume that leadership is a necessary condition to gestate fully developed processes that students express our concern that the leadership is consolidated in the institution as an object of study, we recommend to create spaces for training leaders where students assume responsibility for their commitments to in all democratic settings.